The complete mitochondrial genome of a tessaratomid bug, Eusthenes cupreus (Hemiptera: Heteroptera: Pentatomomorpha: Tessaratomidae) - Song, Wen; Li, Hu; Song, Fan; Liu, Li; Wang, Pei; Xun, Huaizhu; Dai, Xun; Chang, Jian; Cai, Wanzhi (Zootaxa, 2013)
The 16, 299 bp long mitochondrial genome (mitogenome) of a tessaratomid bug, Eusthenes cupreus (Westwood), is reported and analyzed. The mitogenome represents the first sequenced complete mitogenome of the heteropteran family Tessaratomidae. The mitogenome of E. cuopreus is a typical circular DNA molecule with a total AT content of 74.1%, and contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a control region. The gene arrangement is identical with the most common type in insects. Most PCGs start with the typical ATN codon, except that the initiation codon for COI is TTG. All tRNAs possess the typical clover-leaf structure, except tRNASer (AGN), in which the dihydrouridine (DHU) arm forms a simple loop. Six domains with 45 helices and three domains with 27 helices are predicted in the secondary structures of rrnL and rrnS, respectively. The control region is located between rrnS and tRNAIle, including some short microsatellite repeat sequences. In addition, three different repetitive sequences are found in the control region and the tRNAIle-tRNAGln-tRNAMet-ND2 gene cluster. One of the unusual features of this mitogenome is the presence of one tRNAGln-like sequence in the control region. This extra tRNAGln-like sequence is 73 bp long, and the anticodon arm is identical to that of the regular tRNAGln.